2021
DOI: 10.21320/1818-474x-2021-3-108-116
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Gaseous Nitric Oxide to the Extracorporeal Circulation Circuit: Experimental and Clinical Data: a review

Abstract: Introduction. Usually, gaseous nitric oxide (NO) is supplied to the patient by inhalation, adding to the inhaled gas mixture during spontaneous breathing, or supplying it to the inspiratory part of the ventilator. It is believed that the main point of its action is the pulmonary vasculature, where it exhibits an expanding effect, thus improving the oxygenation of arterial blood and reducing the pulmonary artery pressure. However, data from recent experimental clinical studies suggest that the addition of NO di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…A recent study in adult patients after cardiac surgery showed that NO insufflation into the CBP circuit has an ability to prevent AKI [66], but current global data are inconsistent and require further investigation. Otherwise, the measures to prevent kidney damage during cardiac surgery in children are non-specific and boil down to reduced intraoperative damaging factor exposure.…”
Section: Prevention Of Csa-aki In Childrenmentioning
confidence: 99%
“…A recent study in adult patients after cardiac surgery showed that NO insufflation into the CBP circuit has an ability to prevent AKI [66], but current global data are inconsistent and require further investigation. Otherwise, the measures to prevent kidney damage during cardiac surgery in children are non-specific and boil down to reduced intraoperative damaging factor exposure.…”
Section: Prevention Of Csa-aki In Childrenmentioning
confidence: 99%